2019
DOI: 10.1016/j.ipej.2019.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal supraventricular tachycardia

Abstract: Supraventricular tachycardia (SVT) is one of the most common conditions requiring emergency cardiac care in neonates. Atrioventricular reentrant tachycardia utilizing an atrioventricular bypass tract is the most common form of SVT presenting in the neonatal period. There is high likelihood for spontaneous resolution for most of the common arrhythmia substrates in infancy. Pharmacological agents remain as the primary therapy for neonates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 41 publications
2
13
1
3
Order By: Relevance
“…Their report may reflect the true incidence of arrhythmias determined via Holter ECG, yet infrequent PACs or PVCs are arrhythmias that may have resolved spontaneously even when unidentified and untreated. While male infants are considered to have a higher incidence of arrhythmias, 3 , 8 , 9 we did not find any difference in incidence between male and female infants in our study (male, 48%).…”
Section: Discussioncontrasting
confidence: 76%
“…Their report may reflect the true incidence of arrhythmias determined via Holter ECG, yet infrequent PACs or PVCs are arrhythmias that may have resolved spontaneously even when unidentified and untreated. While male infants are considered to have a higher incidence of arrhythmias, 3 , 8 , 9 we did not find any difference in incidence between male and female infants in our study (male, 48%).…”
Section: Discussioncontrasting
confidence: 76%
“…SVT is defined as a narrow QRS complex tachycardia that requires atrial tissue or AV node as an arrhythmia substrate [ 1 ], and the mechanism of development is divided into re-entry and automaticity [ 5 , 6 ]. In children, SVT is mainly caused by the re-entry mechanism; however, it is known that SVT due to the automaticity mechanism is more prevalent in infants than that in children or adolescents and accounts for 15% of total SVT incidents [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“… 4 Among arrhythmias in neonates, the most common is SVT, with an incidence of 1 per 250–1,000 paediatric patients. 5 , 6 Atrial flutter occurs less often, with an incidence of 2.1 per 100,000 live births, and typically does not reoccur after treatment. 4 , 6 While one study of 44 neonates with atrial flutter showed that 25% had a second atrial arrhythmia, none of them had an underlying genetic syndrome.…”
Section: Discussionmentioning
confidence: 99%